2021
DOI: 10.3389/fenvs.2020.575614
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in Sea Turtles, Marine Mammals and Humans: A One Environmental Health Perspective

Abstract: Microplastics are ubiquitous pollutants in the marine environment and a health concern. They are generated directly for commercial purposes or indirectly from the breakdown of larger plastics. Examining a toxicological profile for microplastics is a challenge due to their large variety of physico-chemical properties and toxicological behavior. In addition to their concentration, other parameters such as polymer type, size, shape and color are important to consider in their potential toxicity. Microplastics can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 74 publications
(163 reference statements)
0
29
0
1
Order By: Relevance
“…Moreover, exposure to weathering conditions, such as UV irradiation and physical abrasion, exacerbates the release of MPs ( Wang et al, 2021 ). MPs are ubiquitous in the environment ( Dioses-Salinas et al, 2020 ; Dobaradaran et al, 2018 ; Takdastan et al, 2021 ), and many studies recorded their presence in plankton ( Lin, 2016 ), seaworms ( Missawi et al, 2020 ), earthworms ( Rillig et al, 2017 ), mollusks ( De-la-Torre et al, 2020a ), crustaceans ( Goldstein and Goodwin, 2013 ), fish ( Wang et al, 2020 ), sea turtles and marine mammals ( Meaza et al, 2021 ; Santillán et al, 2020 ). The presence of MPs along the terrestrial and marine food chains suggests that humans are exposed through the consumption of contaminated seafood and food products ( Akhbarizadeh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, exposure to weathering conditions, such as UV irradiation and physical abrasion, exacerbates the release of MPs ( Wang et al, 2021 ). MPs are ubiquitous in the environment ( Dioses-Salinas et al, 2020 ; Dobaradaran et al, 2018 ; Takdastan et al, 2021 ), and many studies recorded their presence in plankton ( Lin, 2016 ), seaworms ( Missawi et al, 2020 ), earthworms ( Rillig et al, 2017 ), mollusks ( De-la-Torre et al, 2020a ), crustaceans ( Goldstein and Goodwin, 2013 ), fish ( Wang et al, 2020 ), sea turtles and marine mammals ( Meaza et al, 2021 ; Santillán et al, 2020 ). The presence of MPs along the terrestrial and marine food chains suggests that humans are exposed through the consumption of contaminated seafood and food products ( Akhbarizadeh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on several factors, the release of MPs (< 5 mm) has been estimated to reach about 2230 MPs per mask, and more than 2.43 × 10 9 PNPs (<1 µm) per mask ( Ma et al, 2021 ). These plastic particles are widely known for their ubiquity in the environment, including water bodies, soil, sediment, atmosphere, and cryosphere ( Dobaradaran et al, 2018 , Akhbarizadeh et al, 2021b , Bergmann et al, 2019 , Dioses-Salinas et al, 2020 , Torres and De-la-Torre, 2021 ), organisms from multiple taxa ( Villagran et al, 2020 , Hall et al, 2015 , Meaza et al, 2021 , Ory et al, 2018 ), mostly due to accidental ingestion, and foods and consumer goods ( De-la-Torre, 2020 , Barboza et al, 2018 , Akhbarizadeh et al, 2020 , Li et al, 2015 ). The ecotoxicological effects of MPs/PNPs have been demonstrated in multiple studies, and are generally associated with oxidative stress, cytotoxicity, neurotoxicity, behavioral changes, among other sublethal effects during the early stages of the development of model organisms ( Webb et al, 2020 , Kim et al, 2021 , Prokić et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Blue PD, particularly microplastics, dominated microplastics found in many species, from freshwater fishes to marine megafauna (e.g. Ory et al 2017;Meaza et al 2020;Zantis et al 2020); but for the same species Arias et al (2019) observed that predominant colors were transparent and red. It was also observed that there was a difference in color distribution depending on locations (Markic et al 2018), which could explain differences found between both areas.…”
Section: A Bmentioning
confidence: 98%